'Re-socialisation' in isolated spaces: A case study on the social organisation of Fangcang shelter hospital patients under extreme spatial conditions. Issue 5 (June 2022) - Li, Jie; Shu, Yeshuo; Chen, Ningkang; Wang, Fang; Li, Hui
Fangcang shelter hospitals – erected by installing medical equipment in large public venues – played an essential role during the COVID-19 pandemic in China. Their isolation, interior density and patients' mutual exposure deviate from normal living conditions, necessitating the study on the adaptation, social organisation and emotional response of patients. For this purpose, we conducted spatial analysis, semi-structured interviews with patients and medical workers and social media mining. We found: (1) Patients were deprived of former identities and equalised upon hospitalisation, which formed the basis of later self-organised hierarchical social relationships. (2) Intimate spatial structures expedited relationship construction among neighbouring patients and facilitated community building by expanding the influence that the more active patients exerted on the passive ones. (3) These social situations generally helped alleviate patients' anxiety. Our study reveals the social and emotional ramifications of such emergency spaces on people, thus providing insight for pandemic response and other global emergencies. It also responds to the theory of 'the production of space' and elucidate the theory of 'total institutions' from a new perspective.